CoBi3: A Binary Cobalt–Bismuth Compound and Superconductor1. Issue 37 (23rd July 2013) - Schwarz, Ulrich; Tencé, Sophie; Janson, Oleg; Koz, Cevriye; Krellner, Cornelius; Burkhardt, Ulrich; Rosner, Helge; Steglich, Frank; Grin, Yuri
<x xml:space="preserve">Abstract</x> The first binary phase in the system Co‐Bi was obtained by high‐pressure high‐temperature synthesis. The NiBi3‐type structure motif comprises cobalt‐centered monocapped bismuth prisms with covalent Co‐Bi interactions. The polyhedra are condensed into infinite columns (see picture), which are arranged in the form of a distorted hexagonal rod packing. The new compound is a superconductor with a Tc slightly below 0.5 K.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>